DocOx (AIO-PK0106): a phase II trial of docetaxel and oxaliplatin as a second line systemic therapy in patients with advanced pancreatic ductal adenocarcinoma. Issue 1 (December 2016) - Ettrich, Thomas; Perkhofer, Lukas; von Wichert, Goetz; Gress, Thomas; Michl, Patrick; Hebart, Holger; Büchner-Steudel, Petra; Geissler, Michael; Muche, Rainer; Danner, Bettina; Kächele, Volker; Berger, Andreas; et al.
Abstract Background The current study was conducted to examine the activity of a docetaxel/oxaliplatin (DocOx) combination as second line treatment for advanced pancreatic ductal adenocarcinoma (Trial registration: NCT00690300. Registered June 2, 2008) Methods DocOx is a prospective, multi-center, single arm, phase II trial using docetaxel (75 mg/m2, 60 min, d 1) and oxaliplatin (80 mg/m2, 120 min, d 2) in 21-day cycles. The treatment period was scheduled for up to 8 cycles. Primary endpoint was tumor response according to RECIST 1.0. Secondary endpoints were progression free survival, overall survival, safety/toxicity, quality of life and clinical benefit. Results Data represent the intention to treat analysis of 44 patients with chemorefractory pancreatic cancer enrolled between 2008 and 2012 at five institutions in Germany. The primary endpoint of tumor response was achieved in 15.9 % of the patients (7 partial remissions, no complete remission), with a disease control rate of 48 % after the first two treatment cycles. Median progression free survival (PFS) was 1.82 months (CI 95 % 1.5–3.96 months) and median overall survival (OS) was 10.1 months (CI 95 % 5.1–14.1 months). Conclusions This single-arm trial demonstrates that the combination of docetaxel and oxaliplatin yields promising results for the treatment of advanced pancreatic ductal adenocarcinoma patients. Selected patients had particular benefit from this treatment as indicated by long PFS and OS times. Even after 8 cycles of treatment with DocOx a partial response was observed in 2 patients and stable disease was observed in another 6 patients. The data obtained with the DocOx protocol compare well with other second line protocols such as OFF (oxaliplatin, 5-FU, leucovorin). The DocOx regimen could be an interesting option for patients who received gemcitabine as first line treatment for metastatic pancreatic cancer.